Tingkah laku pengajaran efektif dan kualiti etika dalam kalangan guru PPSMI di daerah Beluran, Sabah - Ng, Nancy Yut Kuan (2010)
This study is survey for effectiveness of teaching behaviour and ethics of personal quality among PPSMI teachers in Beluran district, Sabah. The effectiveness of teaching behaviour refers to the efficient teaching technics and methods, class and school environment, subject's contents as well as teachers quality of communication with their students. Ethics of personal quality considers by teachers development, reflection, analysis and self development as well as manures moral values as like unity, cooperation, respects with another, consideration and responsibility. It is interconnected by teachers quality attribute as energetic and perceptive, pious, kindness, honest, dedication, high integrity and motivation, loveliness, creative and innovative as well as increase the skillful and teachers professionalism through the courses and seminar. This study performs by questionnaire methods among 100 PPSMI teachers in primary and secondary school at Beluran district. Sample is selected from Reasonable Sampling which choose PPSMI teachers who have teaching at least one year with their school English facilitator. In its entirely, the study method is descriptive survey by using the questionnaire form as the main instrument. It is consist three constructs specifically effectiveness of teaching behaviour, ethics of personal quality and teaching professionalism aspects. By using the SPSS 12.0 for Windows, show us the results that no differentiation between gender and effectiveness of teaching behaviour [t(48) = -1.39, p>.05] and sig= .17 as well as teachers' experience with effective teaching [F(2,47) = 51.25, p>.O5] and sig= .90 and ethics of personal quality [F(2,47) = 0.57, p>.05] by sig= .57 among PPSMl teachers. Otherwise, there are diffrentation between gender and ethics of personal quality [t(29.35) = 1.80, p <. 0.5] by sig = .08.. There are have significant relationship between effectiveness of teaching and teachers professionalism [r(48) = 0.92, p < .01] by sig=.000 but not for ethics of personal quality [r(48)= 0.13, p > .01] and sig= .39 among PPSMI teachers.